2021
DOI: 10.2147/cmar.s336578
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic Implication of Metabolic Syndrome in Patients with Nasopharyngeal Carcinoma: A Large Institution-Based Cohort Study from an Endemic Area

Abstract: Objective Metabolic syndrome has been identified as a prognostic predictor in multiple cancers. This study aimed to evaluate the impact of metabolic syndrome on the clinical outcome of patients with nasopharyngeal carcinoma (NPC) and its mechanism. Methods A cohort of 2003 NPC patients with a median follow-up time of 96.3 months (range: 4.1–120.0 months) were enrolled in this analysis. Kaplan–Meier curves and the Log rank test were used to determine the differences in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 48 publications
1
5
0
Order By: Relevance
“…Among the 181 metabolites significantly changed in the NPC serum, half belongs to lipids and lipid‐like molecules. Some of the 181 metabolites, such as dl ‐glutamic acid, linoleic acid, cholesterol, dl ‐lactate, l ‐pyroglutamic acid, palmitic acid, and arachidonic acid, have been reported to be associated with NPC in previous reports 26–29 . These significantly changed metabolites are enriched in 16 pathways, including biosynthesis of amino acids, biosynthesis of unsaturated fatty acids, and central carbon metabolism in cancer ( p < 0.05).…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Among the 181 metabolites significantly changed in the NPC serum, half belongs to lipids and lipid‐like molecules. Some of the 181 metabolites, such as dl ‐glutamic acid, linoleic acid, cholesterol, dl ‐lactate, l ‐pyroglutamic acid, palmitic acid, and arachidonic acid, have been reported to be associated with NPC in previous reports 26–29 . These significantly changed metabolites are enriched in 16 pathways, including biosynthesis of amino acids, biosynthesis of unsaturated fatty acids, and central carbon metabolism in cancer ( p < 0.05).…”
Section: Discussionmentioning
confidence: 94%
“…Similar to the results in several other studies, pathways such as arginine biosynthesis, biosynthesis of unsaturated fatty acids, D-glutamine and D-glutamate metabolism, fatty acid biosynthesis, and biosynthesis of amino acids were found to be highly associated with NPC development in this study. [26][27][28][29] Cancer-related pathways including aldosterone synthesis and secretion, basal cell carcinoma, cholesterol metabolism, and ferroptosis were also significantly enriched. 30,31 Huang et al reported that cholesterol-derived metabolites and abnormal cholesterol metabolism play important roles in suppressing immune responses and supporting cancer development.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations